2010
DOI: 10.1080/15389581003735600
|View full text |Cite
|
Sign up to set email alerts
|

Volvo and Infiniti Drivers’ Experiences With Select Crash Avoidance Technologies

Abstract: Despite some unnecessary or annoying warnings, most Volvo and Infiniti owners use crash avoidance systems most of the time. Among early adopters, the first requirement of effective warning systems (that owners use the technology) seems largely met. Systems requiring activation by drivers for each trip are used less often. Owner experience with the latest technologies from other automobile manufacturers should be studied, as well as for vehicles on which technologies are standard (versus optional) equipment. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(44 citation statements)
references
References 2 publications
1
42
0
1
Order By: Relevance
“…Participants' higher trust in side-view assist than in other systems in the current study mirrors the large proportion of owners who report they always keep these systems turned on and would want them in their next vehicle (Braitman et al 2010;Cicchino and McCartt 2015). Yet trust differed by implementation even for this system that was most trusted overall.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…Participants' higher trust in side-view assist than in other systems in the current study mirrors the large proportion of owners who report they always keep these systems turned on and would want them in their next vehicle (Braitman et al 2010;Cicchino and McCartt 2015). Yet trust differed by implementation even for this system that was most trusted overall.…”
Section: Discussionmentioning
confidence: 76%
“…Past research has shown that drivers find lane departure warning annoying (Braitman et al 2010;Cicchino and McCartt 2015;Eichelberger and McCartt 2014;, and the current study found that they also do not strongly trust this system either. Annoyance and lukewarm feelings of trust might explain why lane departure warning systems are deactivated more often than other warning systems (Flannagan et al 2016;Reagan and McCartt 2016).…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…It is important to understand whether drivers react appropriately under these circumstances. Survey research has shown that vehicle owners often do not understand the capabilities and limitations of advanced vehicle systems (Jenness, et al, 2008;Braitman, et al, 2010;McDonald, et al, 2016), but there is a need to understand how drivers' knowledge (or lack of knowledge) about vehicle safety systems actually influences driving behavior.…”
Section: Introductionmentioning
confidence: 99%